2006
DOI: 10.1890/0012-9658(2006)87[1856:aplatv]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Look at the Variable Area Transect

Abstract: The variable area transect (VAT) is a plotless density estimator that has received little attention in the ecological literature despite having potentially robust estimation properties. VAT allows for density estimations without the lengthy search times associated with other plotless density estimators. In spite of this, little has been written about the effect of varying transect widths on its density estimation properties or on the practical implementation of the VAT in field settings. An artificial populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…PCQM methods with g ≥ 3 are often impractical in the field. This is because of the difficulty of determining which individual is the g th (Dobrowski, Murphy 2006). In this research, g = 2 was the best.…”
Section: Sampling Methods (Topsis Algorithm)mentioning
confidence: 76%
See 1 more Smart Citation
“…PCQM methods with g ≥ 3 are often impractical in the field. This is because of the difficulty of determining which individual is the g th (Dobrowski, Murphy 2006). In this research, g = 2 was the best.…”
Section: Sampling Methods (Topsis Algorithm)mentioning
confidence: 76%
“…The low RBIAS of VAT sampling is the most important reason for choosing this method. Engeman and Sugihara (1998) and Dobrowski and Murphy (2006) found that the VAT method was robust and more efficient. Kiani et al (2013) showed that the VAT method was the best sampling method in all patterns in terms of RBIAS and time together.…”
Section: Sampling Methods (Accuracy Precision Bias)mentioning
confidence: 99%
“…The method suggested by Borders et al [4] of sampling a fixed number of trees along a variable section of a plantation row may be similar in principle to a variable-length transect. Several simulation studies indicated positive results from variable area transect sampling ( [31][32][33]). However, variable area transects were found to have significant bias towards a clustered spatial distribution by Engman et al [34].…”
Section: Introductionmentioning
confidence: 99%
“…They fall within the family of plotless sampling techniques and have as main advantage their speed of application (Parker ; Engeman et al. ; Dobrowski & Murphy ). These techniques are used mainly in forestry to measure the density of tree stems (overall, per species, per size class, etc.).…”
Section: Introductionmentioning
confidence: 99%